A pediatric brain tumor consortium phase II trial of capecitabine rapidly disintegrating tablets with concomitant radiation therapy in children with newly diagnosed diffuse intrinsic pontine gliomas. Issue 2 (1st November 2017) - Kilburn, Lindsay B.; Kocak, Mehmet; Baxter, Patricia; Poussaint, Tina Young; Paulino, Arnold C.; McIntyre, Christine; Lemenuel‐Diot, Annabelle; Lopez‐Diaz, Christine; Kun, Larry; Chintagumpala, Murali; Su, Jack M.; Broniscer, Alberto; et al.
Abstract: Background: We conducted a phase II study of oral capecitabine rapidly disintegrating tablets given concurrently with radiation therapy (RT) to assess progression‐free survival (PFS) in children with newly diagnosed diffuse intrinsic pontine gliomas (DIPG). Patients and methods: Children 3–17 years with newly diagnosed DIPG were eligible. Capecitabine, 650 mg/m 2 /dose BID (maximum tolerated dose [MTD] in children with concurrent radiation), was administered for 9 weeks starting the first day of RT. Following a 2‐week break, three courses of capecitabine, 1, 250 mg/m 2 /dose BID for 14 days followed by a 7‐day rest, were administered. As prospectively designed, 10 evaluable patients treated at the MTD on the phase I trial were included in the phase II analyses. The design was based on comparison of the PFS distribution to a contemporary historical control (n = 140) with 90% power to detect a 15% absolute improvement in the 1‐year PFS with a type‐1 error rate, α = 0.10. Results: Forty‐four patients were evaluable for the phase II objectives. Capecitabine and RT was well tolerated with low‐grade palmar plantar erythrodyesthesia, increased alanine aminotransferase, cytopenias, and vomiting the most commonly reported toxicities. Findings were significant for earlier progression with 1‐year PFS of 7.21% (SE = 3.47%) in the capecitabine‐treated cohort versus 15.59% (SE = 3.05%) in the historical control ( P  = 0.007), but there was no difference for overall survival (OS) distributions ( P  = 0.30). Tumor enhancement at diagnosis was associated with shorter PFS and OS. Capecitabine was rapidly absorbed and converted to its metabolites. Conclusion: Capecitabine did not improve the outcome for children with newly diagnosed DIPG.